An Analysis of Offender Based Reentry Programs Impact on Crime Rates - Davis, Kenneth; Grant, Tameiko (Advances in Social Sciences Research Journal, 2021)
This case study was based upon the crime reduction efforts of an offender-based treatment coalition in St. Johns County, Florida. The study used a multi-tool qualitative data gathering method to understand if the coalition contributed to crime reductions locally. The research findings concluded that the St. Johns County Re-entry Coalition did positively contribute to crime reductions in the county.